Need for Additional Anesthesia After Single Injection Spinal Analgesia for Labor: A Retrospective Cohort Study. Issue 3 (September 2020) - Sharpe, E.E.; Kim, G.Y.; Vinzant, N.J.; Arendt, K.W.; Hanson, A.C.; Martin, D.P.; Sviggum, H.P.
Abstract : ( Int J Obstet Anesth . 2019;40:45–51) While the most common forms of neuraxial analgesia for labor are continuous epidural and combined spinal-epidural, single injection spinal analgesia is sometimes used for labor analgesia. A disadvantage of the single injection technique is that an additional anesthesia procedure may be needed if labor is prolonged or surgery is required. A previous study reported another anesthetic intervention was needed in 26% of women who received single injection spinal analgesia for labor. This current retrospective study aimed to determine the rate of additional anesthetic interventions in women who received a single injection spinal block for labor analgesia.